SWOT ANALYSIS OF ROMANIA'S APICULTURE - Mircea Adrian GRIGORAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents SWOT analysis of beekeeping in Romania using various results in scientific research and author's critical opinion on the past, present and future of this important sector of agriculture. The paper is based on the data from the National Institute of Statistics and on the study of many published articles closely connected with the topic. The results emphasized that Romania has a long tradition in apiculture, favourable conditions for Apis mellifera carpatica, for pickings in a large range of wild and cultivated flora, good pastoral areas, technological solutions for bee growing and breeding, a high number of bee families and apiarists, a high quality honey production and a potential for organic honey. Romania is facing with a small apiary size, a low honey yield, a weak beekeepers organization in associations, a various apiarists' training level, a non sufficient number of honey collecting centres and brands, and with fake honey. The existence of Apimondia, Apiculturits' Association in Romania, Research and Development Institute, the legislative framework, the EU and National programes for beekeeping development are a guarantee that apiculture will continue to develop in the future. The low internal consumption and the increased demand in the EU as well as the numerous rural population could encourage the business in the field of beekeeping for increasing export and trade balance, the income and living standard in the rural areas. But, the increased price of apiary inputs, the low acquisition price of honey, the severe competition in the EU market between producers and exporters, honey imports from China at dumping prices, climate change and bees diseases are threats which could affect beekeeping in Romania. For increasing productivity and competitiveness of beekeeping, apiarists should apply for financial aids offered by the EU and Romanian Government to grow the number of bee families over 150, to intensify pickings in pastoral, to increase honey production and its quality, to extend organic honey production, to diversify production and develop more local brands, to export a higher honey amount at a better price in the EU and assure a high efficiency along the honey chain.